The syntax-discourse interface : representing and interpreting dependency - Burkhardt, Petra (Linguistik aktuell ;, 2005)
This book combines theoretical and experimental aspects of the establishment of dependency. It provides an account of dependency relations by focusing on the representation and interpretation of referentially dependent elements, particularly regular reflexives, logophors, and pronouns. First, the establishment of dependency is discussed within a model of syntax--discourse correspondences that predicts an economy-based dependency hierarchy contingent on the level of representation at which the dependency is formed as well as the internal structure of the dependent element and its antecedent. Sec.